Promoting E-Learning Platform to Achieve 21st Century Skills in Teaching and Learning Process in School Context - Tantri, Niki Raga; Efendi, Yudi (English Department, Universitas Negeri Surabaya, 2020)
This paper is a conceptual review which discusses the previous literatures employing LMS for the effectiveness of teaching and learning activities in the classroom. Despite the success stories of the implementation of this web-based platform in the academic context, there was few studies highlight the mechanism of using LMS for the classroom management to accommodate effective face to face and online learning for a specific term. Several studies about employing LMS in the classroom were reviewed to obtain the forthcoming proposal of classroom activities using LMS. The review results the elaboration of recent LMS is provided as well as the advantages of using LMS to achieve the 21st century skills are described. Preparation of LMS for teaching and learning activities in the classroom including the learning goals, planning for both face to face and online learning, the current Bloom Taxonomy, selecting online tools, and the evaluation are interpreted to establish future classroom activities.